2020
DOI: 10.1587/transinf.2019edp7305
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of The Similarity of Individual Knowledge and The Comprehension of Partner's Representation during Collaborative Concept Mapping with Reciprocal Kit Build Approach

Abstract: Concept mapping is one of the instructional strategies implemented in collaborative learning to support discourse and learning. While prior studies have established its positive significance on the learning achievements and attitudes of students, they have also discovered that it can lead to students conducting less discussion on conceptual knowledge compared to procedural and team coordination. For instance, some inaccurate ideas are never challenged and can become ingrained. Designing a learning environment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Thus, the concept map in which be decomposed into a kit could help the students focused on important ideas represented by the kit. Extending the concept mapping activity [15] and incorporating Kit-Build into collaborative learning [31,32] could also improve their interaction during learning [21,33] and help students to understand and comprehend the learning material.…”
Section: Kit-build Concept Mapmentioning
confidence: 99%
“…Thus, the concept map in which be decomposed into a kit could help the students focused on important ideas represented by the kit. Extending the concept mapping activity [15] and incorporating Kit-Build into collaborative learning [31,32] could also improve their interaction during learning [21,33] and help students to understand and comprehend the learning material.…”
Section: Kit-build Concept Mapmentioning
confidence: 99%
“…Studies on the practical implementation of Kit-Build in the elementary school science class (Sugihara et al 2012) and English as a Foreign Language (EFL) studies (Alkhateeb et al 2016;Andoko et al 2020) suggested that Kit-Build concept map have many positive impacts towards learning. Additionally, the Kit-Build concept map can be incorporated into a collaborative learning environment to facilitate students' discussion in sharing their knowledge and understanding (Sadita et al 2020b;Sadita et al 2020a;Wunnasri et al 2018).…”
Section: Introductionmentioning
confidence: 99%